Influencing elements of technological adoption: Case study about management in an educational institution - Melo , Caroline Oliveira; Luft, Maria Conceição Melo Silva; Rocha, Ronalty Oliveira (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
This study sought to analyze, from the point of view of educational managers, and based on the TOE framework, the determinants, boosters, and creators of barriers to the adoption and implementation of information and communication technologies within an educational institution. A qualitative, descriptive, and exploratory study was conducted, adopting the single case study as the research strategy. The data were collected through interviews, documentary research, and direct observations, later submitted to content analysis. Considering the TOE framework, the results demonstrate that the main determinants of technological adoption are linked to the environmental context; that the boosting elements are arranged in the organizational context; and that the elements that create barriers involve the organizational and environmental contexts.